A hydrodynamics-assisted remote sensing method for estimating vertical distribution of total suspended matter in lakes: a case study of Poyang Lake - Hui Jiang; Jiawei Ouyang; Yao Liu; Lingfeng Wan; Yungen Sun (Journal of Hydrology, 2026)

Three ectomycorrhizal fungal inoculum modifies the growth performance and tolerance of Quercus nuttallii seedlings under salt stress - Nan Yang; Cheng Wan; Daoyuan Ren; Yan Zhang; Stefano Chelli; Zhengxue Zhu; Silvia Traversari; Giovanni Emiliani; Lingfeng Mao (Forest Ecology and Management, 2026)

The sea level rise of the 8.2 ka event simulated by the iCESM1.3 - Lingfeng Wan; Zhengyu Liu; Chengfei He; Chenyu Zhu; Shaoqing Zhang; Jiuyou Lu; Zhaowei Jing (Climate Dynamics, 2026)

Antarctic circumpolar current evolution and its relation to southern hemisphere westerly winds during the holocene - Lingfeng Wan; Dapeng Li; Chenyu Zhu; Zhengyu Liu; Shaoqing Zhang; Xiaopei Lin; Jiuyou Lu (Climate Dynamics, 2025)

The coupling of ultra-nano oxygenation and in-situ sediment remediation technology jointly promotes phosphorus enrichment and nitrogen removal - Lu Cao; Lingling Wan; Chunhui Xi; Zijun Zhou; Siyang Wang; Lingfeng Cao; Zhicheng Min; Xiankun Chen; Yiyong Zhou; Xiuyun Cao; Chunlei Song (Journal of Water Process Engineering, 2025)

Optimal balance of organic detritus and feed for fish growth and water quality improvement through regulating nutrients cycling - Lu Cao; Lingling Wan; Lingfeng Cao; Zhicheng Min; Yiyong Zhou; Xiuyun Cao; Chunlei Song (Environmental Research, 2024)

Dietary Supplementation of β-Carotene Reveals miRNAs Involved in the Regulation of Carotenoid Metabolism in Crassostrea gigas - Dongfang Sun; Sai Wan; Hong Yu; Lingfeng Kong; Qi Li (Journal of Ocean University of China, 2024)

Relationship between eutrophication and greenhouse gases emission in shallow freshwater lakes - Jingjie Zhang; Lingfeng Cao; Zhenghan Liu; Lingling Wan; Xiuyun Cao; Yiyong Zhou; Chunlei Song (Science of The Total Environment, 2024)

Impact of a gravity wave process on the upper stratospheric ozone valley on the Qinghai-Tibetan Plateau - Jundong Wang; Lingfeng Wan; Shujie Chang; Haotian He (Theoretical and Applied Climatology, 2024)
Atmospheric gravity waves are essential meso-small-scale oscillations that facilitate material exchange within the atmosphere. These waves can significantly affect the ozone layer in the Upper Troposphere and Lower Stratosphere (UTLS) on the Qinghai-Tibetan Plateau. However, the influence of gravity wave dynamic processes on upper stratospheric ozone has rarely been studied. This paper identifies the gravity waves on the Tibetan Plateau based on ECMWF Reanalysis 5 (ERA5) data, analyzes the response of the upper stratospheric ozone to the event, and simulates the dynamic propagation mechanism of gravity waves by the Weather Research and Forecasting (WRF) model. This analysis reveals that between 15:00 and 21:00 UTC on July 29, 2015, gravity waves propagated from the surface of Tibetan Plateau (450 hPa) up to the upper stratosphere (20 − 3 hPa) in an arc-shaped structure and tilted to the east with height. The gravity wave signals started to weaken at 21:00 UTC on the same day. Influenced by the easterly rapids, gravity waves partially broke near 3 hPa at 02:30 UTC on July 30, but gravity wave signals were still present, and gravity waves completely broke and released energy at 04:00 UTC. During this process, ozone in the 20–3 hPa region (upper stratosphere) on the Qinghai-Tibetan Plateau responds well to gravity waves, and the ozone mixing ratio began to drop in ozone concentration 30 min after the partial breakup (03:00 UTC). The ozone dropped drastically by about 0.014 ppmv from 04:00 to 05:00 UTC. The WRF simulation results agree well with ERA5 and accurately capture the intricate characteristics of gravity waves. Furthermore, the breakup of gravity waves caused a total drop in ozone of 0.024 ppmv.

Storage allocation rules to meet shared water demands for optimal operation of reservoir water supply - Fang Wan; Yu Wang; Lingfeng Xiao; Qihui Chai (Irrigation and Drainage, 2023)
The priority principle of storage allocation rules of serial cascade reservoirs within an interbasin water supply can reduce water loss and reduce water supply times. Reasonable balancing curves for reservoirs in parallel are proposed, and the proportional distribution of water is determined to illustrate the optimal allocation rule for different reservoir scheduling periods. The mutation point and slope are used to describe the segmentation of reservoirs in parallel. Finally, the relative optimal water supply rule is obtained. Taking the reservoir groups in the lower reaches of the Luanhe River basin as the research object, the results show that the water supply obtained by the balancing curve is increased by approximately 4% compared with the compensation regulation, and wasted water is reduced by 10%. The results are close to the largest water supply, the annual average wasted water and the guarantee rate obtained by dynamic programming. The suggested method can achieve the operation goal effectively and improve the operation performance of the shared water demands for the reservoir water supply. This article highlights the superior results obtained compared with the current storage allocation rules to meet shared water demands.

Metagenomic insights into feasibility of agricultural wastes on optimizing water quality and natural bait by regulating microbial loop - Lingling Wan; Lingfeng Cao; Chunlei Song; Xiuyun Cao; Yiyong Zhou (Environmental Research, 2023)

Synthesis of Lanthanum-Modified Attapulgite and Its Phosphorus-Fixing Mechanism for Urban Eutrophic Lake - Lingfeng Ye; Ye Li; Cong Liu; Bolin Li; Dongxue Liu; Chang Liu; Jie Wan; Chengbin Fu (Water, Air, & Soil Pollution, 2022)

Study on bioleaching of heavy metals and resource potential from tannery yard sludge - Hang Liu; Kaizhi Yang; Lingfeng Luo; Qian Lu; Yonggui Wu; Meiyan Lan; Youfa Luo; Wan Liang (Environmental Science and Pollution Research, 2021)